Cathodoluminescent images and spectra of single crystals of Y2O2S:Tb3+ and Gd2O2S:Tb3+ nanometer sized phosphor crystals excited in a field emission scanning transmission electron microscope. (May 2015) - Silver, J; Yan, X; Fern, G R; Wilkinson, N
Abstract: Cathodoluminescence (CL) spectra have been collected from single nanometer-sized crystals of Y1.98 Tb0.02 O2 S and Gd1.98 Tb0.02 O2 S using a Gatan Vulcan cathodoluminescence imaging spectrometer. Slight variations observed in the CL spectra taken from the crystals are explained, and discussed in relation to bulk samples.